Literature Review on Non-Pharmacological Intervention for Mild Cognitive Impairment in Korea. - Kim, Ok Hee (Journal of Korean Academy of Psychiatric & Mental Health Nursing (JKPMHN), 2024)
Purpose: Mild Cognitive Impairment (MCI) is one of the risk factors for transition to dementia. This study aimed to review characteristics and results of MCI intervention (non-pharmacological) studies and use them as basic data for effective program development. Methods: This is a literature review on intervention studies of MCI. Search and selection procedure was based on PRIZMA in the Cochran collaboration and NECA. 65 papers were extracted by searching through official domestic journals KISS, Nursing, and DND for the last 10 years (2015~2024) using search words of 'mild cognitive impairment' and 'mild cognitive impairment program'. The suitability of studies was repeatedly verified and 15 papers were finally selected. Results: Cognitive function was significantly improved in all 15 papers and memory was significantly improved in 5 papers. Among them, intervention programs that significantly improved memory were virtual reality based immersion P, computer and workbook, independent board game P, dual-task VR P, and exercise-cognitive combined dual task P. Conclusion: The main symptom of MCI is memory impairment. Interventions used in 15 papers showed significant differences in improving overall cognitive function, with memory improvement verified in only 5 papers. A grounded intervention study on MCI including overseas papers was proposed.